Antimicrobial effectiveness of root canal sealers against Enterococcus faecalis - Paola Castillo-Villagomez; Elizabeth Madla-Cruz; Fanny Lopez-Martinez; Idalia Rodriguez-Delgado; Jorge Jaime Flores-Treviño; Guadalupe Ismael Malagon-Santiago; Myriam Angelica de La Garza-Ramos (Medical Journals Sweden, 2022)
We evaluated four root canal sealers to determine their antimicrobial effectiveness against E. faecalis. The direct contact test was used to measure the effectiveness of the study materials and close contact between bacteria on the kinetics of bacterial growth. The agar diffusion test (ADT) was also performed for comparison. Using one-way ANOVA and the F-test, significant differences between the sealers were confirmed. Whereas BioRoot endodontic sealer had an antimicrobial effect statistically similar to the zinc oxide-eugenol control (p=.99), EndoSequence sealer and AH Plus sealer both had a significantly lower antimicrobial effect than the control (p=.0000266 and p=.0000068, respectively).